Serum Selenium Level in Early Healthy Pregnancy as a Risk Marker of Pregnancy Induced Hypertension - Małgorzata Lewandowska (Nutrients, 2019)
Selenium (Se) is an antioxidant nutrient whose deficiency can influence adverse outcomes of pregnancy. The aim of this study is to determine whether serum Se level in early healthy pregnancy may be a risk marker for pregnancy induced hypertension. We obtained data from our prospective study in which we recruited healthy women in weeks 10−14 of a single pregnancy. In this analysis, we examined 121 women who subsequently developed pregnancy-induced hypertension and matched 363 women who remained normotensive. We measured Se levels (using the ICP-MS technique) in the serum in weeks 10−14 of the pregnancy. The odds ratios of pregnancy-induced hypertension (95% confidence intervals) were calculated using multivariate logistic regression. We found that the mean Se level was lower in the case group compared to the control (57.51 vs. 62.89 μg/L; p = 2.6 × 10−10). Excessive body mass index (BMI) and smoking influenced the estimated odds ratios. In the subgroup of women who had never smoked with normal pre-pregnancy BMI, the adjusted odds ratio (AOR) of pregnancy-induced hypertension was 15.34 (95% CI: 2.73−86.31, p = 0.002) for Se levels in the lowest quartile (≤57.68 µg/L), as compared to the highest quartile (>66.60 µg/L), after adjusting for all the accepted confounders. In the whole cohort, the prognostic value of Se by logistic regression showed that the area under curve (AUC) = 0.814. In our study, one can consider the role of Se as a risk marker of pregnancy-induced hypertension.